508 ELIGIBILITY TO DUAL PATHWAY INHIBITION THERAPY IN PATIENTS WITH CORONARY OR PERIPHERAL ARTERY DISEASE. (15th December 2022) - Greco, Antonio; Laudani, Claudio; Cavallo, Matteo; Vannuzzi, Fabio; Giaquinta, Alessia; Capranzano, Piera; Calvi, Valeria; Isola, Gaetano; Pedullà, Eugenio; Pasquale, Rocco De; Uva, Maurizio Giacinto; Di Cataldo, Antonio; et al.
Abstract: Background: The VOYAGER PAD and COMPASS trials established the benefit of dual pathway inhibition (DPI) with aspirin and low dose rivaroxaban for eligible patients with peripheral artery disease (PAD) undergoing revascularisation and for those with PAD or chronic coronary syndromes (CCS), respectively. However, in-hospital implementation of DPI remains slow in clinical practice, also due to eligibility uncertainties. Purpose: To assess the eligibility to DPI among contemporary patients hospitalised in cardiology and vascular surgery units, and to evaluate clinical outcomes of patients presenting with revascularised PAD according to their eligibility to the DPI strategy. Methods: We analysed data from patients with revascularised PAD included in the prospective institutional RAPID (RivAroxaban for PerIpheral artery Disease) and applied the VOYAGER PAD criteria to identify patients eligible to DPI and the frequency and distribution of exclusion criteria. Clinical outcomes were compared between patients eligible and not eligible to DPI. The primary efficacy outcome was the composite of cardiovascular death, acute limb ischemia, or unplanned limb revascularization, while the primary safety outcome was major bleeding according to the Bleeding Academic Research Consortium definition (i.e., type 3 or 5). Secondary outcomes included the individual components of the primary efficacy outcome, all-cause death, clinically relevant bleeding and minor bleeding. Finally, to explore the residual potential for DPI applicability in clinical practice, COMPASS criteria were also applied to a contemporary CCS cohort from the institutional registry enrolling coronary artery disease patients undergoing invasive management, and the frequency and characteristics of DPI eligibility between PAD and CCS were compared. Results: From May 2021 to August 2022, 122 patients (mean age 70.9±10.1 years, 74.6% male) were included in the RAPID registry. Based on VOYAGER PAD eligibility criteria, 62 patients (50.8%) were eligible to DPI. Main reasons for exclusion were oral anticoagulation (13.1%), prior stroke or transient ischemic attack (11.5%), high bleeding risk (46.7%), or concurrent indications for dual antiplatelet therapy (0.8%). In the CCS registry, 1, 389 patients were enrolled in the same period (mean age 70.3±10.5 years, 75.6% male). CCS patients who were eligible to DPI were 276 (19.9%). Main reasons for exclusion were concurrent need for dual antiplatelet therapy (27.1%), high bleeding risk (44.8%), need for oral anticoagulation (21.4%), severe heart failure (9.9%), absence of CAD or PAD (35.3%), and end-stage renal disease (2.6%). To provide updated follow-up information, clinical outcomes will be made available for presentation on December 2022. Conclusions: Approximately one patient out of two with revascularised PAD and only one fifth of patients with CCS undergoing invasive management were eligible to DPI. According to these results, unlike candidates to the VOYAGER PAD strategy, candidates to the COMPASS strategy are more likely to be identified in an outpatient than hospital setting.